2013
DOI: 10.1161/hypertensionaha.111.00191
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-(1–7) in the Rostral Ventrolateral Medulla Modulates Enhanced Cardiac Sympathetic Afferent Reflex and Sympathetic Activation in Renovascular Hypertensive Rats

Abstract: Abstract-Enhancement of the cardiac sympathetic afferent reflex (CSAR) contributes to sympathetic excitation in hypertension. The aim of the present study was to determine whether angiotensin (Ang)-(1-7) in the rostral ventrolateral medulla (RVLM) modulated the enhanced CSAR and sympathetic activation, and the signaling pathways that mediated these effects in the 2-kidney, 1-clip renovascular hypertension model. Cardiac sympathetic afferent reflex was evaluated using renal sympathetic nerve activity and mean a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
57
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 46 publications
1
57
0
1
Order By: Relevance
“…It has been demonstrated that the sympathetic activity of obese rats (4,24), renovascular hypertensive rats (5,25,26) and SHRs (6,27,28) is enhanced compared with normotensive rats. Hexamethonium is a ganglionic blocker (10,11) and reduces blood pressure in SHR and Wistar rats (8).…”
Section: A B Cmentioning
confidence: 99%
“…It has been demonstrated that the sympathetic activity of obese rats (4,24), renovascular hypertensive rats (5,25,26) and SHRs (6,27,28) is enhanced compared with normotensive rats. Hexamethonium is a ganglionic blocker (10,11) and reduces blood pressure in SHR and Wistar rats (8).…”
Section: A B Cmentioning
confidence: 99%
“…5 The potential mechanism of these effects remains unclear, but may be related to the increased levels of angiotensin-converting enzyme or Ang-(1-7) metabolites, which may also be biologically active. Given the observation by Li et al, 1 one can also speculate that peripheral Ang-(1-7) may enter the central nervous system via the circumventricular organs, just as Ang II has been shown to do. An interesting future study would be to examine the changes in the rostral ventrolateral medulla after peripheral injections of Ang-(1-7) and determine whether Ang-(1-7) does cross the blood-brain barrier via the circumventricular organs.…”
mentioning
confidence: 90%
“…3 The increased Ang-(1-7) and Mas receptor activity in RVLM contributes to the enhanced CSAR and excessive sympathetic activation, which could propel the pathogenesis of hypertension and progression of organ damage in renovascular hypertension. 1 Velkoska et al also have shown that Ang-(1-7) infusion has major adverse effects of increasing blood pressure and accelerating cardiac hypertrophy and fibrosis in rats with subtotal nephrectomy. 4 In addition, Ang-(1-7) causes transition of tubuloepithelial cells into myofibroblasts, which contributes to renal fibrosis.…”
mentioning
confidence: 97%
“…1 It should be noted that we did not investigate the effects of Ang-(1-7) in periphery. The examination of the changes of Ang-(1-7) level in the RVLM after peripheral injection of Ang-(1-7), which was suggested by Velkoska et al might be helpful in determining whether peripheral Ang-(1-7) could cross the blood-brain barrier via the circumventricular organs in the 2-kidney, 1-clip renovascular hypertension model, which requires further study.…”
mentioning
confidence: 99%